2018
DOI: 10.1186/s12957-018-1346-1
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of a hepatocellular carcinoma as a potential late side effect of radiotherapy in a patient treated for Wilms tumor in childhood

Abstract: BackgroundThe development of a second primary tumor is a potential late side effect of radiotherapy. Particularly, an increased risk of secondary cancers, mostly of digestive or breast origin, has been observed in patients treated with high-dose radiotherapy for Wilms tumor (WT) in childhood. However, hepatocellular carcinoma (HCC) has been very rarely described as a potentially radiotherapy-induced tumor. We describe the case of a patient with an aggressive HCC 50 years after the treatment of a WT.Case presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…These tumors developed 15 to 20 years after the treatment of Wilms tumor. Repullo et al [ 28 ] also reported a 49-year-old man with HCC in the inferior right hepatic lobe as a potential late side effect of radiotherapy in a patient treated for Wilms tumor at the age of 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors developed 15 to 20 years after the treatment of Wilms tumor. Repullo et al [ 28 ] also reported a 49-year-old man with HCC in the inferior right hepatic lobe as a potential late side effect of radiotherapy in a patient treated for Wilms tumor at the age of 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Even for HCC patients who undergo surgical therapy, the 5-year survival rate is less than 50% [7]. Chemotherapy and radiotherapy are the main treatments for HCC with multiple side effects [8,9]. HCC has high metastasis and recurrence rates [10].…”
Section: Introductionmentioning
confidence: 99%